2016
DOI: 10.1186/s12969-016-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal body composition, cardiovascular endurance, and muscle strength in pediatric SLE

Abstract: BackgroundChildren with SLE are known to have higher fat mass compared to their peers but there are no published data regarding exercise capacity as measured by cardiovascular endurance and muscle strength. In our pilot study of ten children with SLE, we sought to examine body composition, cardiovascular endurance, and isometric muscle strength.FindingsTen pediatric SLE patients were studied with a mean age of 15.5 years and 90 % female. Percent body fat above 30 %, the recommended normal level in adolescent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…We addressed two key challenges in comparing TM and CE CPET among children, adolescents, and young adults: (1) the difficulty in quantifying the work performed in TM CPET, and (2) useful approaches to scaling CPET results when body size and physiologic function change so dramatically over the course of growth and development (Cooper et al, ; Cooper et al, ). CPET biomarkers are used to assess disease severity, progress, and response to therapy (including exercise prescriptions) across an expanding range of childhood diseases and conditions and across the lifespan (Ploeger et al, ; Pahkala et al, ; Liem et al, ; Sule and Fontaine, ; Cordingley et al, ; Gualano et al, ; Li et al, ). Despite these factors, CPET has failed to fulfil its promise in child health research and clinical practice (Ashish et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We addressed two key challenges in comparing TM and CE CPET among children, adolescents, and young adults: (1) the difficulty in quantifying the work performed in TM CPET, and (2) useful approaches to scaling CPET results when body size and physiologic function change so dramatically over the course of growth and development (Cooper et al, ; Cooper et al, ). CPET biomarkers are used to assess disease severity, progress, and response to therapy (including exercise prescriptions) across an expanding range of childhood diseases and conditions and across the lifespan (Ploeger et al, ; Pahkala et al, ; Liem et al, ; Sule and Fontaine, ; Cordingley et al, ; Gualano et al, ; Li et al, ). Despite these factors, CPET has failed to fulfil its promise in child health research and clinical practice (Ashish et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased lean mass ( P = 0.009, 95% CI) and increased fat mass ( P = 0.009, 95% CI) were strongly associated with fracture risk in our cohort of patients. This has been reflected in studies performed on patients with both juvenile-onset and adult-onset SLE, 8,9,12 suggesting a role for muscle-building exercise as part of the long-term management of such patients, in order to decrease fracture risk. While glucocorticoid therapy may initially be presumed to be the causative factor in such correlations, the association was still present when adjusted for corticosteroid use.…”
Section: Discussionmentioning
confidence: 99%
“…One small cohort study found children with juvenile SLE had significantly decreased levels of muscle mass and strength, correlating with higher levels of renal disease. 8 A fracture rate of 22.58% was identified in another juvenile SLE cohort, with lower lean mass and higher fat mass in patients when compared to controls, and low lean mass being significantly associated with decreased BMD. 9 Evidence for the potential correlation between body composition and fracture risk is even sparser in the adult SLE population.…”
Section: Introductionmentioning
confidence: 89%
“…However, half of the studies in SLE found T LCO was reduced in only a very few patients [93,95,97] while the remainder found abnormal T LCO values in more than half of the patients [92,94,96]. In one of the studies, T LCO was related to the activity of systemic inflammatory processes and disease activity score [94] A CPET was conducted in 10 children with SLE [98]. V′ O 2 peak was reduced in all patients and in 80% of patients the exercise endurance was below the second percentile compared to age-and sex-matched healthy controls.…”
Section: Rheumatological Disordersmentioning
confidence: 99%